Analysis of Policy on Changing Higher Education to University (Case Study at University of Muhammadiyah Sampit) - Anwar, Khairil; In’am, Akhsanul; Khozin, Khozin; Farid, Farid (International Journal of Education, Management, and Technology, 2025)
Analysis of change policies is carried out to improve systems that are running less effectively in an organization. The aim of this research is to describe the management process of changing a college into a case study university at University of Muhammadiyah Sampit. Qualitative research methods using case studies, data collection techniques using interviews, observation and documentation, data processing techniques using data reduction, data presentation and drawing conclusions, as well as data validity techniques using source triangulation. The research results show that; The termination stage is the stage of abandoning changing old policies in the organization. The change initiation stage is the stage of assessing organizational performance and determining the aspects of change that will be carried out. The stage of initiating change is the stage of planning, establishing and implementing new policies as a result of the change. The conclusion is that the policy analysis of changing universities into universities at Muhammadiyah Sampit University can work well if it is carried out effectively, organized and planned.